Partial correction of neutrophil dysfunction by oral galactose therapy in glycogen storage disease type Ib - Letkemann,R; Wittkowski,H; Antonopoulos,A; Podskabi,T; Haslam,SM; Foell,D; Dell,A; Marquardt,T (International Immunopharmacology, 2017)
Glycogen storage disease type Ib (GSD-Ib) is characterized by impaired glucose homeostasis, neutropenia and neutrophil dysfunction.Mass spectrometric glycomic profiling of GSD-Ib neutrophils showed severely truncated N-glycans, lacking galactose. Experiments indicated the hypoglycosylation of the electron transporting subunit of NADPH oxidase, which is crucial for the defense against bacterial infections. In phosphoglucomutase 1 (PGM1) deficiency, an inherited disorder with an enzymatic defect just one metabolic step ahead, hypogalactosylation can be successfully treated by dietary galactose. We hypothesized the same pathomechanism in GSD-Ib and started a therapeutic trial with oral galactose and uridine. The aim was to improve neutrophil dysfunction through the correction of hypoglycosylation in neutrophils. The GSD-Ib patient was treated for 29 weeks. Monitoring included glycomics analysis of the patient's neutrophils and neutrophil function tests including respiratory burst activity, phagocytosis and migration. Although no substantial restoration of neutrophil glycosylation was found, there was partial improvement of respiratory burst activity.